The Correlation between EFL Students’ Vocabulary Knowledge and Reading Comprehension: A Case Study at the English Education Department of Universitas Kristen Indonesia - Manihuruk, David Hotmagasi (JET (Journal of English Teaching), 2020)
This study aimed at investigating the correlation between students ’vocabulary mastery and reading comprehension performance. The population of the study was the whole students at the English Education Department of Universitas Kristen Indonesia. The sample was taken using the cluster sampling technique, i.e., by taking 52 students of Batch 2015, 2016, and Batch 2017 as the participants. Data were collected in May 2019 by administering vocabulary mastery and reading comprehension tests. The instrument’s reliability was tested employing Cronbach Alpha with the results of 0.733 for the vocabulary test and 0.730 for the reading comprehension test, indicating both instruments are reliable. Using Spearman's non-parametric test, the correlation coefficient between the two variables at the sig. (2 tailed) and 0.05 level of significance was 0.014. This indicates there is a positive moderate correlation between vocabulary knowledge and reading comprehension.